Sayyid Honey MSME Development to Increase Trigona Honey Production Capacity - Edo Rantou Wijaya; Novan Hadi Ahmad; Khairul Akli; Wahyuni Amalia; Ridha Luthvina (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Sayyid Madu is an MSME that sells products in the form of quality pure honey which was founded in 2021. This business started with selling trigona honey and apis dorsata honey online, and received a good response from consumers. The good response was especially for the type of trigona honey. This causes the demand for trigona honey to increase rapidly so that better trigona honey-producing bee cultivation techniques are needed. The goal is to get the best quality and increase production capacity. Trigona honey also has the potential to reach national and international markets due to its efficacy in medical cases. As cultivation developed, the number of trigona bee colonies increased from 7 colonies with honey production of approximately 10 kg/month, at the beginning of January there was an addition of 20 colonies. The increase in this colony is expected to produce honey with more production than usual. To produce lots and lots of quality Trigona honey, breeders must have super colonies, namely colonies with large numbers, dense density, aggressiveness and very active activity. The colony of course requires nectar-producing plant vegetation, namely all plants that have flowers. The yield depends on the spring in the forest area where the bees nest. The main problem faced by Sayyid madu SMEs is Trigona honey production which is still minimal and inconsistent. The lack of production of trigona bee honey is caused by food sources that are less available in nature. In addition, the harvesting equipment that is owned is still lacking so that it can hamper harvesting and affect the quality of the honey produced. There are three alternative solutions implemented in this PKM, namely: (1) making artificial vegetation on residential land, (2) procuring dynamo-based manual nectar suction equipment, and (3) logs for beehives.